SYNTHESIS OF PGE SULFIDE STANDARDS FOR LASER ABLATION INDUCTIVELY COUPLED PLASMA MASS SPECTROMETRY (LA-ICP-MS) - Wohlgemuth-Ueberwasser C.C.; Berndt J.; Ballhaus C.; Stotter née Paliulionyte V.; Meisel T. (My University, 2007)
Sulfide compositions with known Re, Os, Ir, Ru, Rh, Pt, and Pd contents are synthesized to be used as standards for noble metal analysis in solid solution in sulfides. Major elements were added as metals and elemental S. The noble metals, i.e. 35 and 60 ppm each, were added as solutions by micro syringe. Following synthesis at 1 atm the sulfides were sintered at 1.5 to 2 GPa to obtain pellets with theoretical density. Aliquots of the pellets were analysed by isotope dilution ICP-MS for bulk Re and platinum-group elements (PGE). The spatial noble metal distribution was investigated with an ArF excimer laser coupled to a single collector ICP mass spectrometer. Sample homogeneity is shown to depend on the metal/S spectrum and the major element composition of the sulfide, as well as on more subtle factors like oxygen partial pressure during synthesis, run temperature, and degree of partial melting. The most homogeneous sulfide composition is a (Fe,Ni)1-xS monosulfide with 5 wt % Ni and 1-sigma variations in 34 S-normalized noble metal count rates of <3.6%. Nearly as homogeneous is a pure Fe1-xS monosulfide with 1-sigma variations in 34S-normalized noble metal count rates of <5.8 %. A Cu-bearing Fe1-xS monosulfide with 2 wt % Cu was found to be considerably more heterogeneous, suggesting that Cu in solid solution in monosulfides promotes noble metal heterogeneity. The sulfide composition least suitable for the synthesis of noble metal sulfide standards is NiS. © Springer-Verlag 2007.
Keywords: LASER-ABLATION-ICP-MS; PISTON CYLINDER; PLATINUM-GROUP-ELEMENTS; PYRRHOTITE; SULFIDE STANDARD MATERIAL